Institutional Capacity - García-Vegas, Ricardo (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
The paper develops the concept of institutional capacity by integrating contributions from political science and public administration. It examines the context motivating the review of this concept, considering social changes, political phenomena since the 2000s, and scientific-technological advancements. The evolution of the concept is described, and a general definition of institutional capacity is proposed, adaptable to the characteristics of each public organization, following an exhaustive literature analysis, highlighting the various approaches used on this subject. A fundamental aspect of the article is the development of institutional capacity components and the presentation of an analytical model based on three levels: the individual, the organization, and the environment. Each level is operationally developed and complemented with the analysis of the following cross-cutting capacities: coordination, cooperation, and communication.